On the Modification of Immunoreactivity of Myelotransplant after Cryopreservation - Goltsev, A. N.; Matsevitaya, I. Yu.; Lutsenko, Ye. D.; Ostankov, M. V.; Dubrava, T. G.; Goltsev, K. A.; Yampolskaya, Ye. Ye. (Problems of Cryobiology and Cryomedicine, 2010)
The comparative analysis of structure-functional characteristics of bone marrow adhesive cells (BMACs) prior to and after cryopreservation was carried out. The data obtained confirm importance of BMACs as a component of myelotransplant with antigenpresenting function in the general mechanism of T-cell activation that induce graft-versus-host reaction (GVHR). The results allow to understand the mechanisms of immune interactions between cryopreserved allomyelotransplant and the recipient's organism and opportunities of applying the cryopreservation of bone marrow for minimization of GVHR.